Acute leukaemia and myelodysplastic syndromes with chromosomal rearrangement involving 11q23 locus, but not MLL gene. Issue 3 (5th August 2016) - Zuo, Wenli; Wang, Sa A; DiNardo, Courtney; Yabe, Mariko; Li, Shaoying; Medeiros, L Jeffrey; Tang, Guilin
Abstract : Aims: Chromosome 11q23 translocations, resulting in MLL (KMT2A ) rearrangement, have been well characterised in acute myeloid leukaemia (AML) and acute lymphoblastic leukaemia (ALL). However, little is known of haematopoietic neoplasms associated with 11q23 translocation but without MLL rearrangement (11q23+/ MLL −). The aim of this study is to characterise such cases with 11q23+/ MLL −. Methods and results: We retrospectively searched our database for cases with haematopoietic malignancies with 11q23+/ MLL −. We identified nine patients, two with AML, two with B-lymphoblastic leukaemia (B-ALL); two with T-lymphoblastic leukaemia (T-ALL), two with myelodysplastic syndrome (MDS) and one with chronic myelomonocytic leukaemia (CMML). The translocations included t(X;11)(p11.2;q23), t(2;11)(p21;q23), t(6;11)(q27;q23), t(8;9;11)(q13;q13;q23), t(11;11)(p15;q23), t(11;14)(q23;q24) and t(11;15)(q23;q14). Five of six patients with acute leukaemia had received chemotherapy and detection of 11q23 translocation occurred at time of disease relapse. Both patients with MDS and the patient with CMML had 11q23 translocation detected at time of initial diagnosis, all three patients progressed to AML after >1 year on hypomethylating agent therapy. All patients received risk-adapted therapies, including stem cell transplant in five patients. At the last follow-up, eight patients died with a median overall survival of 14 months. Conclusions: 11q23+/ MLL − occurs rarely, involving different partner chromosomes and showing clinical and pathological features and disease subtypes different from those cases with MLL rearrangement. 11q23+/ MLL − appears to be associated with clonal evolution/disease progression in acute leukaemia, a high risk for AML progression in MDS/CMML and a high incidence of disease relapse.